EFFECT OF WATER FLOW-RATE ON GROWTH, NUTRIENT UTILIZATION, AND SURVIVAL OF AFRICAN CATFISH FINGERLINGS IN A SEMI-CLOSED SYSTEM - Elaigwu, Audu Michael; Saidu, Abdurrauf; Ochokwu, Ijeoma J. (FUDMA JOURNAL OF SCIENCES, 2025)
The circulation of water by gravity in fish tank is a strategy to reduce the cost of energy in pumping. Thus, this study assessed different water flow-rates on growth, nutrient utilization, survival and condition factor of Clarias gariepinus in semi-closed system. It involved 15 PVC tanks of 120 L each stocked with first weight of 5.10 ± 0.06 g and fed with a commercial feed for 8 weeks under varied water flow rates of 0 L/m, 0.12 L/m, 0.24 L/m, 0.48 L/m and 0.96 L/m in triplicates. Weight gain was significantly (p < 0.05) enhanced from 26.63 ± 0.20 g in the 0 L/m to 121.40 ± 0.25 g in the 0.96 L/m. The highest survival rate of 91.67 ± 4.17 % was noticed in the 0.96 L/m. The feed conversion ratio and condition factor followed the same trend with growth responses. While, the dissolved oxygen was significantly increased from 5.56 ± 0.04 mg.L-1 in the 0 L/m to 8.57 ± 0.03 mg.L-1 in the 0.96 L/m. The PCA1 exhibited a positive correlation in growth responses, survival rate and condition factor, while, feed conversion ratio showed a negative correlation. The RDA recorded observed responses of 82 % reliability in the specific growth rate, condition factor and feed conversion ratio. This study established a significant specific growth rate of 5.71 ± 0.01 %.day-1; condition factor of 1.68 ± 0.02 g.cm3-1 and feed conversion ratio of 1.34 ± 0.04 in the 0.96 L/m.
Keywords: Fish; Dissolved oxygen; Circulation; Tank; System